Design of a Web-Based E-Perpus Information System for The Faculty of Tarbiyah and Teacher Education UIN Sumatera Utara - Lubis, Fitra Hidayat; Siregar , Hervilla Amanda R (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
The Faculty of Tarbiyah and Teacher Training UIN Sumatera Utara requires a more efficient and integrated library management system to support the learning process. The goal of this study is to create an electronic library information system (E-Perpus) that allows lecturers, students, and academics to digitally access library collection information. We designed this information system to streamline the process of searching, borrowing, returning, and managing library collection data. This study employs a system development approach, which involves stages of needs analysis, design, implementation, and system testing. Problems that occur at the research location of the Faculty of Teacher Training and Education UIN Sumatera Utara include difficulties in accessing library information, limitations of the manual system, and lack of data integration. The design process for the web-based E-Perpus application begins with an analysis of user needs, followed by interface design and system development using the Rational Unified Process methodology. We designed this application to streamline the process of searching, borrowing, and returning books. The test results show that the application functions well on various devices, with a responsive and user-friendly interface. Testing was carried out using a black box, and all features ran well. The study yielded a prototype of the E-Perpus application, which includes features for book searching, information availability, online book borrowing and return, and data management for library members. We expect the implementation of this E-Perpus system to enhance library management efficiency and streamline user access to the necessary learning resources.